ANALISIS PENGARUH RASIO CAR, NPL DAN NPM TERHADAP PERTUMBUHAN LABA PADA PT BANK MANDIRI PERSERO - WIJAYA, I KETUT KUSUMA (GANEC SWARA, 2020)
This research was conducted at PT Bank Mandiri Tbk, which is one of the state-owned companies and the largest assets and profits in Indonesia. This study aims to analyze the effect of CAR, NPL and NPM on financial performance. This research is an associative study whose data were collected through literature and documentation studies. Data analysis used Multiple Linear Regression test. The classical assumption test includes normality test, multicollinearity test, heteroscedasticity test, hypothesis testing using the t test and F test.The results showed that Net Profit Margin had an effect on Bank Mandiri's profit growth, while the Capital Adequancy Ratio and Non-Performing Loans had no effect on profit growth.